Relationships Coordination of Eyeyes Hands and Feets with Football Ability in Sepaktakraw Penjaskesrek Students University of Dharmas Indonesia - M Dedi Irawan; Dian Estu Prasetyo; Muhamar kodafi putra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
The problem that occurs in the soccer takraw players at Dharmas Indonesia University is the low ability of the futsal players at Dharmas Indonesia University. So that it has a negative impact when players perform silage, as seen in the results of the silage test, only 9 players out of 10 players reach the maximum score, where the average is only 30.5. These results can be stated as still very low where the average has not been able to reach the maximum value. In addition, these results indicate that there is a problem in the test process regarding sepak takraw on eye, hand and foot coordination so that it has an impact on the results of the silage ability that is not maximized at the time of the test. then when the sepaktakraw players do the soccer test they carry out well and calmly in following the instructions given on the field. Then the lack of student communication when playing sepak takraw and there was a loss of balance in holding the ball. so in doing soccer in the game of sepaktakraw we must understand the techniques and the basics which we can understand from the basics of doing soccer sila